Dividends versus Stock Repurchases and Long-Run Stock Returns under Heterogeneous Beliefs - Bayar, Onur; Chemmanur, Thomas J; Liu, Mark H (The Review of Corporate Finance Studies, 2021)
Abstract We analyze a firm’s choice between dividends and stock repurchases under heterogeneous beliefs. Firm insiders, owning a certain fraction of equity, choose between paying out cash available through a dividend payment or a stock repurchase, and simultaneously choose the scale of the firm’s project. Outsiders have heterogeneous beliefs about project success and may disagree with insiders. In equilibrium, the firm distributes value through dividends alone, through a repurchase alone, or through a combination of both. In some situations, the firm may raise external financing to fund its payout. We also develop results for long-run stock returns following dividends and repurchases. (JEL G32, G35) Received June 2, 2020; editorial decision November 3, 2020 by Editor Andrew Ellul. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.